Hyperpolarization of 15N-pyridinium and 15N-aniline derivatives by using parahydrogen: new opportunities to store nuclear spin polarization in aqueous media. Issue 37 (6th August 2019) - Jagtap, Anil P.; Kaltschnee, Lukas; Glöggler, Stefan
Abstract : We introduce 15 N quaternary pyridinium as moiety that can be NMR-signal-enhanced by several orders of magnitudes and allows for long-term storage of the so gained hyperpolarization in water. Abstract : Hyperpolarization techniques hold the promise to improve the sensitivity of magnetic resonance imaging (MRI) contrast agents by over 10 000-fold. Among these techniques, para-hydrogen induced polarization (PHIP) allows for generating contrast agents within seconds. Typical hyperpolarized contrast agents are traceable for 2–3 minutes only, thus prolonging tracking-times holds great importance for the development of new ways to diagnose and monitor diseases. Here, we report on the design of perdeuterated 15 N-containing molecules with longitudinal relaxation times ( T 1 ) of several minutes. T 1 is a measure for how long hyperpolarization can be stored. In particular, we introduce two new hyperpolarizable families of compounds that we signal enhanced with para-hydrogen: tert -amine aniline derivatives and a quaternary pyridinium compound with 15 N- T 1 of about 8 minutes. Especially the latter compound has great potential for applicability since we achieved 15 N-polarization up to 8% and the pyridinium motif is contained in a variety of drug molecules and is also used in drug delivery systems.